Comparison of residual shunt rates in five devices used to treat patent foramen ovale. Issue 3 (4th March 2014) - Matsumura, Koichiro; Gevorgyan, Rubine; Mangels, Daniel; Masoomi, Reza; Mojadidi, Mohammad Khalid; Tobis, Jonathan
<x xml:space="preserve">Abstract</x> Objectives To assess the effective closure rate among devices used for transcatheter patent foramen ovale (PFO) closure, and to discuss the management of patients with large residual shunts. Background Several devices are used off‐label for transcatheter closure of a PFO in the United States. The rate of residual shunting after PFO closure varies by device. Failure of effective closure poses risk of a recurrent cerebrovascular event, persistent migraine, or recurrent orthodeoxia. Methods Patients who underwent PFO closure in the Cardiac Catheterization Laboratory at UCLA between 2001 and 2013 and had baseline and adequate follow‐up transcranial Doppler studies following device placement were enrolled in the study. Results Of 167 patients whose records were analyzed, effective PFO closure occurred in 90% (150/167) of patients. The highest effective closure rate was with the Amplatzer Septal Occluder (ASO; 100%), followed by the Amplatzer Cribriform (93%), Gore Helex (90%), Amplatzer PFO (86%), and CardioSEAL (86%) device. The highest rate of residual shunting was observed after placement of the 30‐mm Gore Helex device (55%). Of the 17 patients with a residual shunt, three required a repeat PFO closure procedure due to a significant residual shunt associated with recurrent pulmonary emboli or profound orthodeoxia. All three patients received an ASO which successfully closed the residual shunt. Conclusions Transcatheter PFO closure has a high success rate, but a moderate residual shunt occurs in about 10% of cases. The observed incidence of residual shunting after PFO closure is significantly larger with the 30‐mm Helex device. © 2014 Wiley Periodicals, Inc.